Validity and Reliability of a Digital Application Combining LogoTherapy and Cognitive Behavior Therapy for Reducing Anxiety in Hemodialysis Patients with Chronic Kidney Disease - Mugihartadi, Mugihartadi; Said, Faridah Mohd; Nambiar, Nisha (Sahabat Publikasi, 2024)
This study aims to assess the validity and reliability of a digital application that integrates Logotherapy and Cognitive Behavioral Therapy (LCBT) to reduce anxiety in patients with Chronic Kidney Disease (CKD) undergoing hemodialysis. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS) before and after intervention. Content validity was established through expert judgment from mental health professionals and IT specialists, while construct validity was confirmed through statistical analysis. Reliability was evaluated through Cronbach's alpha and test-retest methods. This application demonstrated strong content and construct validity, with a high Cronbach's alpha coefficient indicating excellent internal consistency. Additionally, the application demonstrated significant test-retest reliability, confirming its stability over time. These findings suggest that the LCBT application is a valid and reliable tool for managing anxiety in CKD patients, offering a promising adjunctive treatment to improve psychological outcomes in this vulnerable population.